The problem of hospital malnutrition and its consequences - Pierzak, Monika; Szczukiewicz-Markowska, Grażyna; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2020)
Statistics show that about 35% to 55% patients admitted to a hospital ward are undernourished, 20% of whom are found in the group of patients with severe malnutrition. According to ESPEN (European Society of Parenteral and Enteral Nutrition), ‘Malnutrition is a condition resulting from a lack of absorption or a lack of consumption of nutrients, leading to a change in body composition (the reduction of free fat mass and body cell mass), thus resulting in physical and mental activity impairment and having a negative effect on the treatment of the original condition.’ Taking into consideration the serious health and socio-economic consequences related to malnutrition, a priority of the health care policy of every country should involve a targeted active response aimed at impelling hospital authorities and health care decision-makers to devise relevant hospital malnutrition battle plans and strategies. The aim of this paper is to presentat the consequences related to faulty screening of the nutritional status of hospitalised patients.